FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PASIEN GAGAL GINJAL KRONIS TERHADAP PROGRAM HEMODIALISA DI RUMAH SAKIT “X” - Suzanna Fabella Putri; Haryanti (STIKes IMC Bintaro, 2018)
Background: Chronic renal failure is a progressive decrease in kidney function within months or years. In the late-stage condition requires hemodialysis action Chronic Kidney Disease (CKD) is a state of decline in kidney function that is chronic, progressive and persist for a long time. Several years on this condition the kidney loses its ability to maintain volume and body fluids in the state of normal dietary intake. Goal: The purpose of this study was to determine the factors that influence the compliance of patients with chronic renal failure to hemodialysis program at “X” Hospital. Method: This research uses quantitative method with analytical survey with cross sectional approach and using chi-square test. Result: The results of this study found that most of the 60% of respondents who are not adherent to hemodialysis program compared with respondents who obediently undergo hemodialysis program. The conclusion of this study is a significant relationship between family support, age, and education of respondents with adherence to hemodialysis program. While the sex and the work of the respondent there is no relation with compliance to the hemodialysis program.